Protocol: Filgotinib in addition to methotrexate versus filgotinib monotherapy in patients with rheumatoid arthritis with an inadequate response to methotrexate: A multicenter, prospective, open-label, randomized controlled trial (FAITHFUL Study) - Mitsuhiro Akiyama; Toshihiko Hidaka; Motohide Kaneko; Satoshi Ito; Hiroaki Taguchi; Tomonori Ishii; Shuji Asai; Shintaro Hirata; Kei Ikeda; Katsuya Suzuki; Naoki Kato; Yuko Kaneko (PLoS ONE, 2025)
Background Filgotinib (FIL), a Janus kinase-1 preferential inhibitor, has been studied for its efficacy and safety in rheumatoid arthritis. The FINCH3 trial compared FIL monotherapy, FIL plus methotrexate (MTX) combination therapy, and MTX monotherapy in MTX-naïve patients. However, comparisons in patients with an inadequate response to MTX remain unclear. This study aims to evaluate the efficacy and safety of FIL plus MTX versus FIL monotherapy in patients with rheumatoid arthritis who have an inadequate response to MTX. Methods and analysis FAITHFUL (Filgotinib Add-on versus swITcH to Filgotinib in patients with rheUmatoid arthritis who inadequateLy responded to methotrexate) study is a phase IV multicenter, prospective, open-label, randomized controlled trial. Patients with a history of inadequate response to at least 8 weeks of MTX and moderate or high disease activity will be assessed for eligibility at 10 centers in Japan. A history of Janus kinase inhibitor use is an exclusion criterion, but prior use of biologic agents is not considered. Enrolled patients will be randomly assigned in a 1:1 ratio to either the group adding FIL (Add-on group) or the group switching to FIL monotherapy (Switch group). The target sample size is 120 participants. The primary endpoint is the change in DAS28-CRP from baseline to week 24, aiming to assess if the Switch group is non-inferior to the Add-on group. Safety will be evaluated by assessing the incidence of adverse events. Ethics and dissemination The study has received approval from the Certified Review Board of Keio University Hospital (N20230002) and adheres to the principles outlined in the Declaration of Helsinki and good clinical practice standards. Prior to enrollment, all participants provide written informed consent. The findings from this study are intended to be submitted for publication in relevant peer-reviewed journals. Trial registration The trial was registered at Japan Registry of Clinical Trials (jRCTs031230673).